PENYULUHAN DAN PELATIHAN FISIOTERAPI PADA KONDISI DE’QUERVAIN SYNDROME DENGAN TERAPI LATIHAN DI KOMUNITAS KELUARGA DESA LESES SAWANGAN KECAMATAN GRINGSING KABUPATEN BATANG - Nur Susanti; Ayu pangestuningtyas (LPPM Universitas Pekalongan, 2022)
De Quervain syndrome is a disease with pain in the area of the styloideus process due to chronic inflammation of the tendon wrapping of the abductor polysis longus muscle and the extensor of the brevis polysis at the distal radius and the clamping of the two tendons. From the observation process of identifying physiotherapy problems in patients by lecturers and students of Physiotherapy, conducted by interviewing the community, it was found that the common problem experienced by patients was pain in the thumb. Situation analysis in the form of observations carried out by all teams in the family community, gringsing sub-district, Batang district in the form of interviews with the family community, the process of observing the identification of physiotherapy problems in De Quervain syndrome using lecture and question and answer methods, the purpose of this activity is to increase knowledge and understand the family community about the role of physiotherapy in patients, especially in reducing pain in the thumb. The solution offered by the team uses counseling and training methods to reduce pain in De Quervain syndrome with exercise therapy to increase muscle strength, the implementation of outreach activities is attended by ten family members, before the counseling and training process is given a pre-test and a post-test that is rejected. measure for people who understand the extension is carried out. The results of the pre-test and post-test proved that the level of understanding after counseling increased. It can be concluded that after being given counseling and physiotherapy training in De Quervain syndrome with exercise therapy in increasing muscle strength, there is an increase in muscle strength and the range of motion of the joints.Keywords: De Quervain syndrome, exercise therapy